Endocrine disrupting chemicals and their impact on reproductive functions - Darasz , Dominika; Wróbel, Bartosz; Wójcik, Lena; Zając, Dominik; Łobaziewicz , Marek; Żołyński , Michał (Journal of Education, Health and Sport, 2026)
Background. Compounds that disrupt the functioning of the endocrine system (EDC - endocrine disrupting chemicals) are widespread in the environment. Their ubiquitous presence and increasingly common use in many industries and economies prompt numerous attempts to characterize their biological effects. From the point of view of public health, the impact of EDCs on the functioning of the reproductive system - both in childhood and adulthood - is considered one of the most important. Purpose of the study. The aim of the study was to collect and analyze publications focusing on the impact of endocrine-disrupting compounds on reproductive functions - with particular emphasis on the process of sexual maturation, fertility and reproduction. Material and methods. A review of the literature available on PubMed was performed using various combinations of keywords: ’EDC/endocrine disrupting chemicals’ + ’puberty’, ’EDC/endocrine disrupting chemicals + ’fertilily’, ’EDC’ + ’pregnancy’, ’EDC/endocrine disrupting chemicals’ + ’reproduction’ and others. Results. The analysis of the collected publications allows to conclude that EDCs have a multidirectional biological effect on the human body, affecting all stages of hormonal action - synthesis, metabolism, the process of binding to the receptor and many others. The role of EDCs has been confirmed in the pathogenesis of many autoimmune, metabolic and structural disorders. Conclusions. EDCs, as widely distributed compounds that disrupt the functioning of the endocrine system, are a promising direction for research on processes and disorders important from the point of view of public health, for which reproductive health is one of the most important areas of interest.